Determination of tributyltin at parts-per-trillion levels in natural waters by second-order multivariate calibration and fluorescence spectroscopy - Bravo, M. (2013)
This work presents a non-sophisticated approach for the trace determination of tributyltin, the most toxic organotin species, in very interfering environments, combining fluorescence measurements of its morin complex and the selectivity of second-order chemometric algorithms. The power of MCR-ALS (multivariate curve resolution/alternating least-squares) to quantify tributyltin through fluorescence excitation-emission matrices in the presence of its main degradation products and of a pool of additional twenty-three metal ions is demonstrated. The applied algorithm successfully faces the challenge of solving the strong overlapping among the spectra of the several sample components. The proposed methodology was applied to tap, river, lagoon and seawater spiked samples, obtaining satisfactory results at ngL -1 levels, after a pre-concentration step on a C18 membrane, demonstrating the analytical potential of the proposed methodology.